Production of Eco-friendly Liquid Hand Soap Using Local Products for Community Empowerment - Anwar, M. Syaiful; Oktofan, Niko Ilham; Yu, Chen Bao (STAI Miftahul ULa Nganjuk, 2024)
This community service project aimed to empower the Sedati, Sidoarjo community by producing eco-friendly liquid hand soap using local ingredients, specifically